Case Study of Next-Generation Artificial Intelligence in Medical Image Diagnosis Based on Cloud Computing - Wu, Jiang; Wang, Hongbo; Ni, Chunhe; Zhang, Chenwei; Lu, Wenran (Journal of Theory and Practice of Engineering Science, 2024)
Cloud computing technology is a computing model based on the Internet, which can provide elastic, scalable, reliable and secure computing, storage and network resources to meet the various computing needs of enterprises and individuals. Cloud computing technology has become an important driving force for enterprise digital transformation and innovation. Through cloud computing technology, enterprises can run their business more efficiently, reduce costs, increase productivity, protect data and systems from attacks and leaks, keep systems always available, open new markets, and more. At the same time, cloud computing technology has also brought more innovation opportunities, such as artificial intelligence, big data and the Internet of Things, so as to help enterprises better meet customer needs and explore new markets. In addition, cloud computing combined with artificial intelligence has brought a lot of convenience to many traditional industries, such as medical care, education, and scientific research. By lowering barriers to entry, cloud computing levels the playing field and makes it easier for these businesses to compete with established players. With the wide application of technologies such as 5G, artificial intelligence, big data and the Internet of Things, cloud computing infrastructure will become more popular and powerful, but also face more challenges and opportunities. We need to constantly pay attention to the evolution trend of cloud computing and actively respond to new challenges and opportunities, so as to better use cloud computing technology to promote the development and innovation of enterprises and achieve sustainable development. In this paper, by analyzing the practical application cases of the next generation intelligence combined with cloud computing to the medical image analysis and diagnosis industry, the future prospects of cloud computing and next generation artificial intelligence are expounded.